PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS DAN KOMPOSISI ASET TERHADAP KECURANGAN PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Nabila Soviatul Fitria; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research was the purpose of knowing the effect of Leverage, Profitability, Liquidity, and Asset Composition on Fraudulent Financial Reporting in manufacturing companies listed on the Indonesian Stock Exchange for the period 2018-2020. This research using logistic regression analysis. The result in this study is indicate that simultaneously Leverage, Profitability, Liquidity, and Asset Composition has effect on Fraudulent Financial Reporting. Leverage and Profitability. Meanwhile partially shows that Leverage and Profitability has effect on Fraudulent Financial Reporting. Liquidity and Asset Composition has no effect on Fraudulent Financial Reporting.Keywords: Leverage, Profitability, Liquidity, Asset Composition, Fraudulent Financial Reporting